Ab initio study of germanium-hydride compounds under high pressure. Issue 25 (21st March 2015) - Hou, PuGeng; Tian, FuBo; Li, Da; Zhao, ZhongLong; Duan, DeFang; Zhang, HuaDi; Sha, XiaoJing; Liu, BingBing; Cui, Tian
<x xml:space="preserve">Abstract</x> Motivated by the potential high-temperature superconductivity in hydrogen-rich materials and phase transitions, germanium-hydride compounds under high pressure were studied by a genetic algorithm.